Weed–pathogen interactions and elevated CO2: growth changes in favour of the biological control agent. (13th March 2014) - Shabbir, A; Dhileepan, K; Khan, N; Adkins, S W; Bailey, Karen
Summary In this study, we used Parthenium hysterophorus and one of its biological control agents, the winter rust (Puccinia abrupta var. partheniicola) as a model system to investigate how the weed may respond to infection under a climate change scenario involving an elevated atmospheric CO2 (550 μmol mol−1) concentration. Under such a scenario, P. hysterophorus plants grew significantly taller (52%) and produced more biomass (55%) than under the ambient atmospheric CO2 concentration (380 μmol mol−1). Following winter rust infection, biomass production was reduced by 17% under the ambient and by 30% under the elevated atmospheric CO2 concentration. The production of branches and leaf area was significantly increased by 62% and 120%, under the elevated as compared with ambient CO2 concentration, but unaffected by rust infection under either condition. The photosynthesis and water use efficiency (WUE) of P. hysterophorus plants were increased by 94% and 400%, under the elevated as compared with the ambient atmospheric CO2 concentration. However, in the rust‐infected plants, the photosynthesis and WUE decreased by 18% and 28%, respectively, under the elevated CO2 and were unaffected by the ambient atmospheric CO2 concentration. The results suggest that although P. hysterophorus will benefit from a future climate involving an elevation of the atmospheric CO2 concentration, it is also likely that the winter rust will perform more effectively as a biological control agent under these same conditions.